INNOVATIVE APPLICATION OF TRADITIONAL BAMBOO WEAVING IN MODERN FURNITURE DESIGN - YU, Z.; PASHKEVYCH, K. L. (Art and Design, 2023)
Of the study is to explore the approaches and strategies of integrating traditional bamboo weaving elements into modern furniture design. The methodology of this paper is based on a literature review and a case study analysis. The literature review provides a theoretical framework and a historical background of bamboo weaving as a traditional craft and a cultural expression. The case study analysis examines examples of modern furniture designs that use bamboo weaving as a main or complementary element, and evaluates their functionality, aesthetics and sustainability. The paper uses qualitative and descriptive methods to analyze the data and draw conclusion. This paper summarized the two visual expression forms of traditional bamboo weaving in furniture design and put forward three application principles and innovative methods of bamboo weaving in modern furniture design. Based on the attributes of bamboo weaving culture and technology, this article summarized the expression form, application principles and innovative methods of traditional bamboo weaving applied to modern furniture design. This article provides some methods of combining traditional craft and modern design for designers, which can enhance the cultural value and aesthetic appeal of furniture products. It also contributes to the preservation and inheritance of bamboo weaving as a traditional skill and a cultural heritage, which can enrich the diversity and vitality of contemporary design culture.